2019
DOI: 10.2174/1568026619666181130135703
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Neuroimaging Studies on Working Memory Paradigms in Patients with Bipolar Disorder

Abstract: New brain technologies including neuroimaging studies are powerful means for providing new insights into clinical and cognitive neuroscience. Bipolar disorder is a severe chronic phasic mental disease characterized by various cognitive dysfunctions. Working memory is one prominent domain of cognitive impairment in bipolar disorder. Disruptions in working memory are observed even in euthymic bipolar patients which makes it a potential endophenotypic marker for the disorder. Finding such markers may help in prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The importance of the ACC has been highlighted in studies of adult and youth with BD (Hibar et al., 2018 ; Phillips & Swartz, 2014 ; Toma, Islam, et al, 2019 ). Other regions identified in significant voxel‐wise clusters, including the rostral middle frontal gyrus, vlPFC, and lateral orbitofrontal cortex (OFC), are involved in emotion regulation, working memory, decision‐making, impulsivity, and reward function—all domains known to be impaired in BD (Beshkovet al., 2018 ; Chau et al., 2018 ; Lima et al., 2018 ; Rolls, 2019 ). Cortical thinning and volumetric reductions are well‐documented in these regions in both adolescent and adult BD (Hibar et al., 2018 ; Niu et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the ACC has been highlighted in studies of adult and youth with BD (Hibar et al., 2018 ; Phillips & Swartz, 2014 ; Toma, Islam, et al, 2019 ). Other regions identified in significant voxel‐wise clusters, including the rostral middle frontal gyrus, vlPFC, and lateral orbitofrontal cortex (OFC), are involved in emotion regulation, working memory, decision‐making, impulsivity, and reward function—all domains known to be impaired in BD (Beshkovet al., 2018 ; Chau et al., 2018 ; Lima et al., 2018 ; Rolls, 2019 ). Cortical thinning and volumetric reductions are well‐documented in these regions in both adolescent and adult BD (Hibar et al., 2018 ; Niu et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is considered that left supramarginal gyrus plays a key role of the short-term memory network, preserving an abstract representation of information from serial orders, regardless of content information (19)(20)(21). As functional magnetic resonance imaging has become an important and reliable tool for investigation of brain anatomy and its function in health and disease, it becomes clear that further research of neurobiological basis of cognitive and memory domains can clarify different diagnostic prototypes and thus explain the human brain impairments in neuropsychological patients, since these are characterized by various cognitive dysfunctions (22,23).…”
Section: Discussionmentioning
confidence: 99%
“… 78 However, abnormalities in these brain regions may lead to working memory deficits in patients with bipolar disorder. 79 Both cross-sectional 7 and longitudinal studies 80 showed that patients in acute mood states exhibited reduced activation in the dlPFC and parietal lobe and failed deactivation in the mPFC, while patients in euthymic states exhibited normalisation of the dlPFC and parietal lobe and failed normalisation of mPFC. 80 This evidence indicates that reduced dlPFC and parietal lobe activation may serve as a state characteristic and failure of mPFC deactivation as a trait marker of bipolar disorder.…”
Section: Functional Neuroimaging Studies Comparing Individuals With B...mentioning
confidence: 99%